Analisis Sifat Mekanis Beton High Volume Fly Ash Concrete Dengan Campuran Abu Sekam Padi - Darmawan, Kiki, Mochamad Solikin, S.T., M.T., Ph.D, Muhammad Ujianto, S.T., M.T (2016)
Concrete including the most important material in a construction. The study is intended to replace part of cement by utilizing waste coal power plant called fly ash, in addition to the rice husk ash is added, with HVFAC technology. In general, the compressive strength of concrete HVFAC lower than normal therefore the added material used rice husk ash. In testing the compressive strength and tensile strength sides used the test object with a diameter of 15 cm, height 30 cm with concrete quality f'c = 25 MPa while the water uptake test specimens are used with a diameter of 10 cm, high compressive strength 5. Tests performed on 28 days and 56 days while testing the tensile strength divided and water uptake at the age of 56 days. Concrete design method used by ACI. Variations on concrete testing, (1) normal concrete (2) HVFA + superplasticizer (3) HVFA + superplasticizer rice husk ash. (4) HVFA + + rice husk ash without superplasticizer. Fly ash is fly ash used class F. After testing the tensile strength of concrete at 28 days was highest quality of concrete on concrete HVFA. Do comparative analysis between normal concrete with a concrete mixture HVFA. Meanwhile, at the age of 56 days HVFA lower compressive strength than normal concrete. The use of rice husk ash can not fix the concrete compressive strength either using superplasticizer, and without superplasticizer. The average tensile strength obtained divisive produce comparable value between normal concrete with a variety of other concrete. In the water absorption test of the use of rice husk ash to increase the value of water absorption, low water uptake occurs in HVFA without rice husk ash. Keywords: mechanical properties of concrete, normal strength concrete, fly ash, rice husk ash, superplasticizer.